MTERMS 2016 GATHERS GLOBAL EXPERTS IN TISSUE ENGINEERING AND REGENERATIVE MEDICINE FOR KNOWLEDGE-SHARING AND INFORMATION UPDATES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 17 November 2016 – With the theme "Ensuring Sustainability through Innovative Regenerative Technologies," this conference reflects the commitment of Universiti Sains Malaysia (USM) in promoting innovations and scientific achievements through sustainable approaches.